Analisis Determinasi Kebijakan Dividen Pada Perusahaan LQ45 - Muhammad Nur Adli; Utaminingtyas, Tri Hesti; Khairunnisa, Hera (LPPM Universitas Negeri Jakarta, 2024)
This research aims to test and analyze management ownership, profitability, investment opportunity set, debt to equity ratio, and dividend policy. In order to get secondary data sources for this study, purposive selection techniques were applied to the company's annual report on companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) for the years 2018–2022. The analytic approach used is panel data regression utilizing Econometric Views 13 (EViews) software. The findings indicated that the policy regarding dividends was not affected by the management's ownership of the company, the set of investment opportunities, the impact of profitability, the debt to equity ratio, or the disclosure of sustainability reports.